1989
DOI: 10.1128/mcb.9.8.3385
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the p53 transformation-related protein in mouse fibrosarcoma cell lines: effects of protein sequence and intracellular environment.

Abstract: The transformation-related protein p53 is normally very labile. The stability of p53 is significantly increased in a number of fibrosarcoma cell lines derived from mouse tumors induced by treatment with physical or chemical agents. In many instances, p53 stabilization is correlated with the ability to form a stable complex with the heat shock protein cognate hsc7O. We describe a line in which p53 is very stable yet has no detectable interaction with hsc7O. The inability to form such a complex probably resides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…Complex formation with T antigen (and HSP70) does not directly stabilize p53 (Halevy et al, 1989). Moreover, E1A does not form a complex with p53 (Debbas and White, 1993).…”
Section: Inactivation By Oncoproteins Stabilizes Wt P53mentioning
confidence: 99%
“…Complex formation with T antigen (and HSP70) does not directly stabilize p53 (Halevy et al, 1989). Moreover, E1A does not form a complex with p53 (Debbas and White, 1993).…”
Section: Inactivation By Oncoproteins Stabilizes Wt P53mentioning
confidence: 99%
“…206 The p53 gene is frequently mutated in a variety of tumors including hematologic malignancies. 132,133,207,208 Unlike functional p53, which is rapidly degraded within 5 to 20 min after its synthesis, 209 mutant versions of the proteins have a half-life of 4 to 8 h 210 and accumulate in the cells, thus becoming immunohistochemically detectable.…”
Section: Role Of P53 In Atllmentioning
confidence: 99%
“…Previous studies have suggested that the turnover rate of mutant p53 is at least in part dependent on the cellular context indicated by the fact that tumor mutants have a signi®cantly shortened half-life in wt p53 containing cells than in cells devoid of wt p53 (Halevy et al, 1989;Midgley and Lane, 1997). This hypothesis is strongly supported by the present study (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the expression of tumor derived mutant p53 proteins in wt p53 containing cells had suggested that degradation of p53 is dependent on the cellular environment (Halevy et al, 1989;Midgley and Lane, 1997). To test this hypothesis, the D62 ± 96 form of wt p53 was stably expressed in a number of cell lines which di er in their endogenous p53 status.…”
Section: The Half-life Of P53 Is Dependent On the Cellular Environmentmentioning
confidence: 99%
See 1 more Smart Citation